THE EFFECT OF TIMES, EXPOSURE DURATION, AND PERCEPTION TO BLUE LIGHT EFFECTIVENESS ON INCREASING ALERTNESS - Talitha Rahma, Karyma
Research that examines blue light in tropical countries is limited to nighttime activities where there is an increasing drowsiness. Some studies of blue light in non-tropical countries are also carried out in the morning and afternoon that give significant results on increasing alertness. This research is conducted to determine the effect of times, duration and positive perception to blue light effectiveness on increasing alertness. This research method is an experiment with within-subject design. Twenty participants participated in the experiment in reading activities with independent variables namely lighting conditions (white light and blue light), duration of exposure (30 minutes and 60 minutes), and time of exposure (morning, afternoon, and night), and the dependent variables namely brain wave activity. Perception of blue light was measured at the end of the whole experiment by using a questionnaire that measured perceptions of usefulness, perceived comfort, relaxation and pleasure, and intention to use. The results showed a significant interaction between lighting conditions, duration, and time of exposure to alpha waves (F = 4.569; p <0.05). These results indicate that 60 minutes of blue light exposure significantly decreases alpha activity compared to 30 minutes of blue light exposure at night. Seventy percent of the participants found that blue light gives usefulness, gives comfort, makes relaxing and pleasantness, and shows greater awareness than 30% of them. The conclusion of this study is that blue light is more effective in increasing alertness when given at night activities with a long duration and blue light can be accepted by participants.